A Review of Micellar Enhanced Ultrafiltration Technique in the Removal of Heavy Metals from Aqueous Solutions - Deniz ŞAHİN (Journal of Chemical Engineering Research Updates, 2020)
The pollution of the aquatic ecosystems with heavy metal ions has become a global problem in recent years. Heavy metals normally occur in nature and are essential to life at trace levels. However, they can be toxic when their concentrations exceed the upper permissible limits. Heavy metal contaminated habitats have the ability to bioaccumulate in aquatic ecosystems, which, in turn, may enter into the food chain and lead to health problems. Therefore, it is necessary to remove these heavy metals from aquatic ecosystems. Several technologies are already in operation, but these conventional technologies involve high operational costs and may produce harmful impacts on aquatic ecosystems. Micellar enhanced ultrafiltration (MEUF) is an alternative technique to remove the trace concentrations of heavy metals from aquatic ecosystems. The uniqueness of MEUF is that it requires less energy due to low membrane cost and working pressure. Although various researchers have been carried out the MEUF study on the removal of heavy metal ions, few review papers indicate the factors on MEUF technique. That is the reason why this article focuses on reviewing of different parameters such as membranes, surfactants, operating conditions in the MEUF technique. In this technique, heavy metal ions’ removal even at lower concentrations has reached over 99%, which is evidently demonstrated in the presented review. The use of water-soluble ligands in combination with MEUF is a hybrid process to remove selectively and enhance the recovery of heavy metals. As understood in this study, an investigation is needed to treat highly concentrated solutions and real wastewater.